2018
DOI: 10.3892/or.2018.6537
|View full text |Cite
|
Sign up to set email alerts
|

HOXA5 is a tumor suppressor gene that is decreased in gastric cancer

Abstract: The abnormal expression of homeobox A5 (HOXA5) has been observed in breast and colon cancer; however, the clinical significance of HOXA5 in gastric cancer (GC) is not yet clear. In this study, we found that HOXA5 expression was decreased in GC tissues at the mRNA and protein level compared with paracancerous tissues using reverse transcription-quantitative PCR (RT-qPCR) and western blot analysis, respectively. Immunohistochemistry and Kaplan-Meier survival analysis confirmed that the underexpression of HOXA5 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…Here, we revealed that Hoxa5 was direct target of miR-19a-3p and contribute to miR-19a-3p-induced BMSC osteogenic differentiation. Hoxa5 was served as tumor suppressor in a number of cancers including non-small cell lung cancer [28], osteosarcoma [29], gastric cancer [30] and gastric cancer [31]. Hoxa5 was also reported to alleviate inflammation and induce adipose tissue browning [32].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we revealed that Hoxa5 was direct target of miR-19a-3p and contribute to miR-19a-3p-induced BMSC osteogenic differentiation. Hoxa5 was served as tumor suppressor in a number of cancers including non-small cell lung cancer [28], osteosarcoma [29], gastric cancer [30] and gastric cancer [31]. Hoxa5 was also reported to alleviate inflammation and induce adipose tissue browning [32].…”
Section: Discussionmentioning
confidence: 99%
“…HOXD10 suppresses the migration and invasion of GC cells through insulin-like growth factor binding protein-3 (IGFBP3) and RhoC-AKT pathway (36,39). HOXA5 suppresses GC progression by inhibiting the G1/S transition during the cell cycle (17). HOXA13 promotes GC development via TGF-β, ERK1/2, MDM2-p53-MRP1 pathways, and Wnt/β-catenin signalling (23,(41)(42)(43).…”
Section: Publication Biasmentioning
confidence: 99%
“…All included studies were from China, Japan and Korea, and published between 2012 and 2019. These studies involve the following HOX proteins: HOXB9 (15), HOXD10 (16), HOXA5 (17,18), HOXA10 (19)(20)(21), HOXA13 (22,23), HOXC6 (24), HOXB7 (25,26), HOXA1 (27), HOXA9 (28), HOXC9 (29), HOXC10(30), HOXD4 (31), HOXA11 (32) and HOXD9 (33). These studies explored the prognostic value of HOX proteins expression for OS or disease-free survival (DFS), and the correlation between HOX proteins expression and clinicopathological parameters in GC.…”
Section: Study Characteristicsmentioning
confidence: 99%